(untitled) (Annals of Medical Research, 2021)
Aim: Epstein-Barr virus (EBV) is an infectious agent that affects more than 95% of the world’s population and is usually diagnosed through characteristic clinical findings, hematologic changes in complete blood counts, and atypical lymphocytes in peripheral smears. A definitive diagnosis requires serological confirmation of the EBV infection. This study intends to investigate the relationship between the mean platelet volume (MPV), platelet distribution width (PDW) and plateletcrit (PCT) values, which are platelet indices that can be used as markers of inflammation in different inflammatory diseases, and the EBV-associated infectious mononucleosis (IM) disease.Material and Methods: A total of 54 patients (30 males, 24 females) with EBV-associated infectious mononucleosis diagnosed at the Department of Pediatrics, University of Gaziantep University between January 2015 and June 2017 were retrospectively analyzed. Meanwhile, 68 age and gender-matched children were involved as the control group. White blood cell (WBC), hemoglobin (Hb), MPV, PDW and PCT values were compared across the patient and control group.Results: While the MPV values of the EBV-associated IM patient group were significantly high, the PDW values were significantly low (p0.001). The mean (WBC) counts of the IM patients were higher than those of the control group (p0.001). There was no significant difference between the groups in terms of PCT, platelet and Hb values. Conclusion: According to our findings, PDW and particularly MPV may be useful markers of inflammation during EBV-associated IM.